การลงทุนต่างประเทศจากประเทศกำลังพัฒนาในรัฐสังคมนิยม : ศึกษากรณีการลงทุนของบรรษัทข้ามชาติไทยในสาธารณรัฐสังคมนิยมเวียดนาม - วิทวัส บูรณะ (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
This research aimed to inspect the influences of economic globalization on the socialist state by studying investment of Multinational Corporations (MNCs) from Less Developed Countries (LDCs) investing in socialist state. The research employed Thai’s MNCs (CP, SCG and Thai Summit) investing in Vietnam as the case study. The purposes of the research were to explore the impact of economic globalization representing by MNCs on Vietnam, and whether Thai’s MNCs were entitled as international political actor. This research used qualitative methodology by conducting in-depth interview of 49 key informants as well as documents. The findings revealed that Vietnam was unbale to avoid the influences of economic globalization. However, there are three important elements, namely, the authoritarian nature of political system, the Confucian values and nationalism . These elements have equipped Vietnam with strength and immunity in order to act strategically. The findings also revealed that at the beginning, only CP possessed the international political actor characteristic as the nature of its business and the technological strengths were consistent with the agricultural problems beset Vietnam thus CP was the part of the solutions. SCG philosophy of doing business was not consistent with the international political actor’s nature. Thai Summit was not international political actor as its business was in automotive international production chains where the role of Vietnamese government was already supportive. In terms of their operation up to now, CP’s political actor role vanished as the agricultural problem solved while SCG was still in no place near international political actor’s role. However, SCG utilized its strength in Thailand’s political actor to push SCG project through in Vietnam. Thai Summit still maintained its character from the beginning.